(untitled) (Al-Mansour Journal, 2025)
In this research, the multi-period probabilistic inventory model will be applied to the stores of raw materials used in the leather industry at the General Company for Leather Industries. The raw materials are: Natural leather includes cowhide, whether imported or local, buffalo leather, lamb leather, goat skin, chamois (raw materials made from natural leather), polished leather (raw materials made from natural leather), artificial leather (skai), supplements which include: (cuffs - Clocks - hands - pockets), and threads. This model was built after testing and determining the distribution of demand during the supply period (waiting period) for each material and completely independently from the rest of the materials, as none of the above materials is affected by the other in the supply process. This testing was done using the statistical package program, and then the optimal order quantity that was requested in each batch and for each item is determined, which is known as the optimal economic size of the order, and the reorder point was determined for each item. After that, the total storage costs were compared between the method used in managing stores in this factory and the model that was built, as the cost of using the probabilistic model was less than the method used by the company in managing the demand.